Can loud noise cause acoustic neuroma? Analysis of the INTERPHONE study in France. Issue 7 (15th March 2009) - Hours, M; Bernard, M; Arslan, M; Montestrucq, L; Richardson, L; Deltour, I; Cardis, E
Abstract : Objectives: To investigate possible associations between risk of acoustic neuroma and exposure to loud noise in leisure and occupational settings. Methods: A case-control study was conducted in France within the international INTERPHONE study. The cases were the 108 subjects diagnosed with acoustic neuroma between 1 June 2000 and 31 August 2003. Two controls per case were selected from the electoral rolls and individually matched for gender, age (5 years) and area (local authority district) of residence at the time of the case diagnosis. Multivariate analyses were conducted using conditional logistic regression. Adjustment was made for socioeconomic status. Results: Acoustic neuroma was found to be associated with loud noise exposure (odds ratio (OR) = 2.55; 95% CI 1.35 to 4.82), both in leisure settings, particularly when listening to loud music (OR = 3.88; 95% CI 1.48 to 10.17) and at work (OR = 2.26; 95% CI 1.08 to 4.72). This risk increased with exposure duration (>6 years' leisure exposure: OR = 3.15; 95% CI 1.07 to 9.24). Risk varied according to the type of noise (continuous or explosive vs intermittent). Conclusion: The present results agree with other recent reports implicating loud noise in the risk of acoustic neuroma.